Gaya Kepemimpinan Ideal Dalam Mengelola Konflik Di Lembaga Pendidikan Islam - Indri; Haryanto, Sigit (Universitas Muhammadiyah Surakarta, 2025)
Leadership in Islamic educational institutions plays a crucial role in fostering organizational harmony and effectiveness, particularly in managing conflicts. This study aims to identify the ideal leadership style for conflict management in Islamic educational institutions through an empirical qualitative approach. Data were collected through observation, in-depth interviews, and document analysis at several Islamic educational institutions. The findings indicate that transformational and participative leadership styles are more effective in resolving conflicts compared to authoritarian or laissez-faire approaches. Leaders who demonstrate strong communication skills, actively listen to diverse perspectives, and make fair decisions tend to create a more conducive working environment. This study highlights that adopting adaptive leadership styles grounded in Islamic values can enhance conflict management within Islamic educational institutions. Keywords: leadership, conflict, Islamic education